A holistic investigation into healthcare service quality using a multi-stakeholder approach: The case of Parirenyatwa Hospital - Mubayiwa, Frank (School of Management Studies, 2024)
Service quality is a matter of concern for everyone. As such, understanding the differences in perceptions about service quality provision becomes pertinent, especially under the conditions of the COVID-19 pandemic. One of the questions at stake is whether patients' perceptions should be given equal weight with those of healthcare practitioners, given that patients may not be able to comprehend the technical aspects of healthcare service quality. This study explored the perspectives of both parties in healthcare service delivery, in a multispecialty hospital setting of the Parirenyatwa Group of Hospitals. A cross-sectional research design, encompassing the collection of quantitative data using a questionnaire, was used. Convenience sampling was used to select participants to complete the online questionnaire. The respondents (patients and healthcare practitioners) received a pop-up message prompting them to click and complete the online questionnaire on Qualtrics. The results show that the perspectives of healthcare practitioners and patients differed on four of the five dimensions of the HEALTHQUAL scale, namely, efficiency of healthcare service, improvement of care service, tangible evidence, and safety. The improvement of care and efficiency of healthcare service dimensions both had a large effect size, whilst the tangible and safety dimensions both had a medium effect size. This study was a novel attempt to simultaneously assess healthcare service quality from the perspectives of both patients and healthcare practitioners who are directly involved in the treatment of patients. The research, therefore, provided a holistic view of healthcare service quality in a particular context.